ORIENTASI NILAI BUDAYA PADA KONDISI INEQUALITY: Studi Pada Komunitas yang Berpotensi Konflik Seputar Taman Nasional Teso Nilo (TNTN) - Asriawandari, Hesti (Universitas Lancang Kuning, 2016)
This paper seeks to study the anomic behavior that emerges from and thet value orientation that precedes the latent intercomrnunity conflict in thi: regions affected by the expansion of the Tesso Nilo National Park ir Pelalawan regency, Riau province. In accordance with Johan Galtung: theory of conflict and violence, this paper will expose the cultural ana structural violence that creates an invisible conflict in the society. r1 structural analysis will explain the existence of pressures on any attempt le achieve welfare and the difference in subsistence ability. On the other hand a cultural analysis will discuss the value orientation differences between communities that disrupt social relation and integration. Adaptive behavior that emerges from any social inequality is preceded by a value orientation system and communal attitude.